Dietary Patterns During Pregnancy are Associated with Gestational Weight Gain. - Shin, Dayeon; Lee, Kyung; Song, Won (Maternal & Child Health Journal, 2016)
Objective The role of diet during pregnancy on gestational weight gain is unclear. This study aimed to evaluate the hypothesis that dietary patterns during pregnancy are differentially associated with the adequacy of gestational weight gain at different stages of pregnancy. Methods A total of 391 pregnant women in National Health and Nutrition Examination Survey (NHANES) 2003-2006 were included. Dietary intake was obtained using a National Cancer Institute's food-frequency questionnaire. Results Three dietary patterns were identified by factor analysis with 36 food groups among pregnant women, and they were named according to food group factor loadings: 'mixed', 'healthy', and 'western'. The 'mixed' pattern characterized by a high intake of meat, dairy products, fruits, vegetables, potatoes, nuts and seeds and sweets. After adjusting for maternal sociodemographic variables and physical activity level, women in the highest tertile of 'mixed' pattern score had significantly greater odds of being in the inadequate gestational weight gain compared to those in the lowest tertile (adjusted odds ratio (AOR) 4.72; 95 % CI 1.07-20.94). Women in the mid tertile of the 'mixed' pattern had significantly lower odds of being in the excessive gestational weight gain compared to those in the lowest tertile (AOR 0.39; 95 % CI 0.15-0.99). Conclusion These results suggest that a diet high in meat, dairy products, fruits, vegetables, potatoes, and nuts and seeds during pregnancy might be associated with reducing excessive gestational weight gain.